Studi Literatur tentang Pengelolaan Konflik Nilai dalam Budaya Organisasi Global serta Dampaknya terhadap Keharmonisan Kerja di Perusahaan Multinasional - Shadina Ningrum; Trie Yunike; One Olivia Kusumawati; Dian Prihardini Wibawa (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Value conflict in multinational corporations has emerged as a critical issue alongside the intensification of cross-cultural interactions that are not fully matched by managerial readiness to address differences in values. Existing studies tend to examine organizational culture, conflict, and work harmony separately, resulting in a fragmented understanding and the absence of an integrated analytical framework. Employing a qualitative approach through a literature review of relevant scholarly sources, this article synthesizes the dynamics of value conflict, the role of organizational culture, and its management strategies in a global context. The findings indicate that value conflict arises not only from intercultural miscommunication and ethnocentrism but also from structural tensions between global value standardization and local value adaptation. These conflicts significantly affect work harmony by reducing trust, team cohesion, and collaborative effectiveness. Nevertheless, value conflict also holds constructive potential when managed through inclusive leadership, the development of cultural and emotional intelligence, and adaptive human resource policies. The primary contribution of this study lies in integrating micro, meso, and macro perspectives to provide a more comprehensive conceptual framework for understanding and managing value conflict in multinational organizations.